2017
DOI: 10.18632/oncotarget.21107
|View full text |Cite
|
Sign up to set email alerts
|

Association of melatonin membrane receptor 1A/1B gene polymorphisms with the occurrence and metastasis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a prevalent primary neoplasm of the liver, whose heterogeneous global incidence suggests the likely impact of genetic variations among individuals on the susceptibility to this disease. Increasing evidence indicates that melatonin exhibits oncostatic properties in many cancer types at least in part mediated by its membrane-bound receptors, melatonin receptor 1A (encoded by MTNR1A) and 1B (MTNR1B). In this study, the effect of melatonin receptor gene polymorphisms on the risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…81 A specific haplotype of four MT 2 SNPs was also associated with HCC development, indicating that functions of receptors and melatonin signaling may be associated with HCC development. 81 During 12:12 light-dark cycle, exposure to blue-enriched light (increased transmittance of 462-484 nm and decreased red light greater than 640 nm) at daytime using blue-tinted cages increased plasma levels of melatonin at nighttime in rats. 82 This blue light treatment followed by promotion of melatonin secretion at night inhibited tumor growth in xenograft rat models with Morris 7288CTC hepatoma although detailed mechanisms are undefined.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…81 A specific haplotype of four MT 2 SNPs was also associated with HCC development, indicating that functions of receptors and melatonin signaling may be associated with HCC development. 81 During 12:12 light-dark cycle, exposure to blue-enriched light (increased transmittance of 462-484 nm and decreased red light greater than 640 nm) at daytime using blue-tinted cages increased plasma levels of melatonin at nighttime in rats. 82 This blue light treatment followed by promotion of melatonin secretion at night inhibited tumor growth in xenograft rat models with Morris 7288CTC hepatoma although detailed mechanisms are undefined.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…HCC tumors often have genetic mutations in various genes or their promoters such as telomerase reverse transcriptase ( TERT ), tumor protein p53 ( TP53 ), and catenin beta 1 ( CTNNB1 ) . A previous study using 335 HCC patients and 1196 control individuals has identified single nucleotide polymorphisms (SNPs) in MT 1 melatonin receptor, which are associated with the elevated risk of HCC . A specific haplotype of four MT 2 SNPs was also associated with HCC development, indicating that functions of receptors and melatonin signaling may be associated with HCC development .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 When a single-nucleotide difference is present in the shared sequence of a gene between the individuals of a species or the paired chromosomes in an individual, a singlenucleotide polymorphism (SNP) develops. [9][10][11] Genetic polymorphisms can affect promoter activity or change the encoded amino acids in a protein when arising in the related coding sequence, thus influencing gene expression. 12 The SNPs may play critical roles in the occurrence and development of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of melatonin on the development of HCC is demonstrated by the fact that it protects from the stages prior to liver tumor development (liver injuries, steatosis, NAFLD, fibrosis, cirrhosis, as mentioned previously). Studies with human biopsies of patients with HCC confirm this effect with the finding of a correlation between Single Nucleotide Polymorphisms (SNPs) in MT1 and MT2 and a higher risk of developing HCC [ 304 ]. Among other evidence supporting this protective effect of the indoleamine on the development of HCC is the fact that melatonin can inhibit the proliferation, migration, and invasion capacities of Huh7 and HepG2 hepatoma cell lines by inducing the expression of the miRNA let7i-3p, which reduces Raf1 expression, eventually reducing the activation of mitogen-activated protein kinase signaling downstream from RAF1 [ 305 ].…”
Section: Melatonin: Reported Actions In Breast Prostate Liver Amentioning
confidence: 96%